(untitled) (International Journal of Architecture and Urbanism, 2023)
Geographically, Indonesia is the largest country in the archipelago. The length of Indonesia’s main coastline is known to reach 81,000 km. Based on these results, a fishery management area is needed that is appropriate and as high as possible to ensure the management of fisheries that are rich in marine animals. Pantai Labu Fish Auction Place is a potential place for fisheries. The marine sector is quite large, including capture fisheries, power culture fisheries the processing and marketing of fishery products. As well as supported by Supervision and other activities. One of the Fish Landing Places in Deli Serdang Regency is Pantai Labu Fish Auction Place. Fishing in Pantai Labu is important because the livelihood of most Paluh Sibaji people is fishing. However, the situation at the fish auction may have improved, leaving many customers feeling unhappy. Not only buyers but fishermen, the main actors in this fish auction site, also need qualified facilities. The application of ecological architecture in the renewal of the Fish Auction Place is one way to be applied in the future. Ecological architecture is vital in designing this fish landing site because an environmental architecture uses natural elements closely related to this Fish Auction Place.